Development of Multidisciplinary Anticoagulation Management Guidelines for Patients Receiving Durable Mechanical Circulatory Support - Levesque, Amy A. (Clin Appl Thromb Hemost, 2019)
Patients receiving durable mechanical circulatory support (MCS) require life-long anticoagulation with a vitamin K antagonist (VKA). Due to alternations in hemostasis, concomitant therapy with antiplatelet agents and critical illness, they are at increased risk of thromboembolic and bleeding complications compared with the general population managed on VKAs. To prevent thrombotic events, current guidelines recommend that patients with MCS receive long-term anticoagulation with a VKA to maintain a target international normalized ratio (INR) as specified by device manufacturers, but limited data exist regarding specific routine management of anticoagulation therapy and its potential complications. To optimize anticoagulation management and minimize risk in these patients, we have centralized anticoagulation management in a collaborative approach between the inpatient hemostatic and antithrombotic (HAT) stewardship service and between ambulatory anticoagulation management service (AMS) and the advanced heart disease team. Patients are followed by these three services beginning when the device is implanted and extending the duration that patients have the device. The teams include multiple clinicians from cardiac surgery, cardiology, hematology, pharmacy, nursing, case management, nutrition, and psychiatry, therefore, in order to standardize practice among clinicians without compromising patient centered decision making, we assembled an interdisciplinary team to create multiple treatment guidelines. In addition to a centralized and collaborative approach, our guidelines ensure seamless transitions of care between the inpatient and outpatient settings. We believe our approach has demontrated a positive improvement in the care of these challenging patients. In this article, we present our comprehensive centralized anticoagulation management approach for patients with left ventricular assist systems (LVAS).